Synthesis and Properties of some New 5-Fluoro-6-(heterocyclyl) Benzofuroxans - El-Abadelah, M.M.; Nazer, M.Z.; El-Abadla, N.S.; Awadallah, A.M. (Asian Journal of Chemistry, 2012)
A series of 5-fluoro-6-(heterocyclyl) benzofuroxans (3b-e) have been prepared by hypochlorite oxidative cyclization of the respective 4-fluoro 5-(N-heterocyclyl)-2-nitroanilines (2b-e). The heterocyclyls include piprazine, N-(2-hydroxyethyl)piprazine, morpholine and thiomorpholine. Some bio-properties and spectral data these new derivatives are presented.